Age-Related Clinical Spectrum of Plasmodium knowlesi Malaria and Predictors of Severity. (5th March 2018) - Grigg, Matthew J; William, Timothy; Barber, Bridget E; Rajahram, Giri S; Menon, Jayaram; Schimann, Emma; Piera, Kim; Wilkes, Christopher S; Patel, Kaajal; Chandna, Arjun; Drakeley, Christopher J; Yeo, Tsin W; et al.
Abstract : Patients with knowlesi malaria were older and had lower parasitemia compared to human-only species. Severe knowlesi malaria occurred only in adults. Anemia was common in children despite lower parasitemia. Parasitemia predicted disease severity: Intravenous artesunate is warranted initially for parasitemia>15000/μL. Abstract: Background: Plasmodium knowlesi is increasingly reported in Southeast Asia, but prospective studies of its clinical spectrum in children and comparison with autochthonous human-only Plasmodium species are lacking. Methods: Over 3.5 years, we prospectively assessed patients of any age with molecularly–confirmed Plasmodium monoinfection presenting to 3 district hospitals in Sabah, Malaysia. Results: Of 481 knowlesi, 172 vivax, and 96 falciparum malaria cases enrolled, 44 (9%), 71 (41%), and 31 (32%) children aged ≤12 years. Median parasitemia was lower in knowlesi malaria (2480/μL [interquartile range, 538–8481/μL]) than in falciparum (9600/μL; P < .001) and vivax malaria. In P. knowlesi, World Health Organization–defined anemia was present in 82% (95% confidence interval [CI], 67%–92%) of children vs 36% (95% CI, 31%–41%) of adults. Severe knowlesi malaria occurred in 6.4% (95% CI, 3.9%–8.3%) of adults but not in children; the commenst severity criterion was acute kideny injury. No patient had coma. Age, parasitemia, schizont proportion, abdominal pain, and dyspnea were independently associated with severe knowlesi malaria, with parasitemia >15000/μL the best predictor (adjusted odds ratio, 16.1; negative predictive value, 98.5%; P < .001). Two knowlesi-related adult deaths occurred (fatality rate: 4.2/1000 adults). Conclusions: Age distribution and parasitemia differed markedly in knowlesi malaria compared to human-only species, with both uncomplicated and severe disease occurring at low parasitemia. Severe knowlesi malaria occurred only in adults; however, anemia was more common in children despite lower parasitemia. Parasitemia independently predicted knowlesi disease severity: Intravenous artesunate is warranted initially for those with parasitemia >15000/μL.